2015
DOI: 10.1099/ijsem.0.000652
|View full text |Cite
|
Sign up to set email alerts
|

Luteimonas soli sp. nov., isolated from farmland soil

Abstract: A yellow-pigmented bacterial strain, designated Y2T , was isolated from farmland soil in Bengbu, Anhui province, China. Cells of strain Y2 T were Gram-stain-negative, strictly aerobic, non-motile and rod-shaped. Strain Y2 T grew optimally at pH 7.0, 30 8C and in the presence of 2 % (w/v) NaCl. The DNA G+C content was 68.9 mol%. The major fatty acids (.5 %) were iso-C 15 : 0 , iso-C 17 : 0 , summed feature 9 (C 16 : 0 10-methyl and/or iso-C 17 : 1 v9c), iso-C 11 : 0 3-OH and iso-C 11 : 0 . The major respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Shange et al [68] found that Actinomycetales (O) showed the largest RAs from soils with the lowest SOM values; Actinomycetales (O) is also an important member of the N cycling community [69]. Luteimonas (G) growth occurs from pH 5-9, with optimal growth at pH 7.0 [70]. Simmons, et al [71] found Luteimonas (G) RAs were increased in unfertilized soil compared to soil amended with green waste compost.…”
Section: Discussionmentioning
confidence: 99%
“…Shange et al [68] found that Actinomycetales (O) showed the largest RAs from soils with the lowest SOM values; Actinomycetales (O) is also an important member of the N cycling community [69]. Luteimonas (G) growth occurs from pH 5-9, with optimal growth at pH 7.0 [70]. Simmons, et al [71] found Luteimonas (G) RAs were increased in unfertilized soil compared to soil amended with green waste compost.…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of Prevotella may replace affected by its phylotype or host ages [22]. Luteimonas, found in three group (C_F, C_D, and H_D) is frequently found in diverse environment such as soil, wastewater, and ammonia biofilter [23]. Certain genus candidate B-42, Halomonas, and Luteimo nas newly detected in this study.…”
Section: Genus (%) Cattle Horsementioning
confidence: 63%
“…The genus Pseudolabrys was previously reported to increase in relative abundance after NK treatment [63]. Luteimonas species are known for their catalytic activities related to oxidase, catalase, alkaline phosphatase, esterase, and esterase lipase and are involved in the biodegradation metabolism of the organic matter [64][65][66]. The enrichment of Luteimonas in soil is a valuable indicator of soil amelioration [67].…”
Section: Discussionmentioning
confidence: 99%